Isolated Distal Fibular Stress Fracture after Total Hip Arthroplasty in a Patient with Developmental Dysplasia of the Hip - Tomofumi Nishino; Fumi Ochiai; Tomohiro Yoshizawa; Hajime Mishima; Masashi Yamazaki (Case Reports in Orthopedics)
Stress fractures following total hip arthroplasty in the lower limbs away from the surgical area are very rare. We report a case of stress fracture in the isolated distal fibula that presented five months after total hip arthroplasty in a patient with developmental dysplasia of the hip. A 67-year-old woman diagnosed with coxarthrosis of the right hip joint, classified as Crowe’s group 3, underwent total hip arthroplasty with acetabular reconstruction using a bulk bone graft. The surgery successfully treated the preoperative leg length discrepancy and flexion and external rotation contractures. The alignment of the right lower limbs changed from slight varus to valgus knee following surgery. The postoperative process went well; however, she experienced lateral ankle pain on the affected side five months after surgery. No obvious fracture was observed via radiograph; however, she received a subsequent diagnosis of isolated distal fibula stress fracture. Additionally, she was diagnosed with vitamin D deficiency. Valgus alignment change of the knee joint and vitamin D deficiency were considered the main causes of the stress fracture. Stress fractures should be suspected in patients complaining of unexpected pain following total hip arthroplasty, even in distant areas of the affected limb, especially in osteoporotic patients.